2020
DOI: 10.1038/s41467-020-19581-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical transplantation using negative pressure ventilation ex situ lung perfusion with extended criteria donor lungs

Abstract: Lung transplantation remains the best treatment option for end-stage lung disease; however, is limited by a shortage of donor grafts. Ex situ lung perfusion, also known as ex vivo lung perfusion, has been shown to allow for the safe evaluation and reconditioning of extended criteria donor lungs, increasing donor utilization. Negative pressure ventilation ex situ lung perfusion has been shown, preclinically, to result in less ventilator-induced lung injury than positive pressure ventilation. Here we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Mesenchymal stromal (stem) cells and their extracellular vesicles have also been proposed as a therapeutic for reconditioning ECD lungs and ameliorating ischemia-reperfusion injury [ 83 , 84 ]. Furthermore, novel approaches to improve EVLP are actively being investigated, such as negative pressure ventilation (NPV) and sub-normothermic temperatures to overcome some of the ventilator and metabolic injuries sustained during EVLP [ 85 , 86 ].…”
Section: Ex Vivo Lung Perfusionmentioning
confidence: 99%
“…Mesenchymal stromal (stem) cells and their extracellular vesicles have also been proposed as a therapeutic for reconditioning ECD lungs and ameliorating ischemia-reperfusion injury [ 83 , 84 ]. Furthermore, novel approaches to improve EVLP are actively being investigated, such as negative pressure ventilation (NPV) and sub-normothermic temperatures to overcome some of the ventilator and metabolic injuries sustained during EVLP [ 85 , 86 ].…”
Section: Ex Vivo Lung Perfusionmentioning
confidence: 99%
“…The aim was to develop a form of ESLP that reduced the incidence of ventilator-induced lung injury (VILI)-a mechanically induced pulmonary edema caused by high respiratory pressures and a documented consequence of prolonged PPV-ESLP [157][158][159]. A recent clinical trial demonstrated that NPV is safe when used to recondition extended criteria donor lungs from transplantation [160].…”
Section: Negative Pressure Ventilation (Npv) Versus Positive Pressure Ventilation (Ppv) Eslpmentioning
confidence: 99%
“…In 2020, Buchko et al established the clinical safety and feasibility of EVOSS technology through a single-center clinical trial of NPV-ESLP whereby twelve extended criteria donor lungs were successfully reconditioned and transplanted into recipients, resulting in 100% 30-day and 1-year survival [160]. Recruitment took place between October 2018 to July 2019.…”
Section: Npv-eslp and Extended Criteria Donorsmentioning
confidence: 99%
“…Conceptually, it is the rate of change of the lung volume with respects to the applied pressure. For NPV, it can be found using (1).…”
Section: B Evlp Device and Ventilation Measurementsmentioning
confidence: 99%
“…Lung transplantation remains the best treatment option for end stage severe pulmonary conditions, such as pulmonary fibrosis caused by SARS-COVID-2 [1]. Unfortunately, this treatment option is underutilized in part due to high rates of donor lung rejection over concerns of transplant viability.…”
Section: Introductionmentioning
confidence: 99%